Research of total antioxidant activity of vegetable oils - Usatyuk, Svitlana; Pelekhova, Lyubov (My University, 2013)
The paper is devoted to research of total antioxidant activity of vegetable oils. Робота присвячена дослідженню загальної антиоксидантної активності рослинних олій.
Keywords: antioxidant action; антиоксидантна дія; vegetable oil; рослинні олії; кафедра експертизи харчових продуктів